2016
DOI: 10.5937/kgjmath1601113z
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities for the polar derivative of a polynomial with restricted zeros

Abstract: Abstract. For a polynomial p(z) of degree n, we consider an operator In this paper we extend above inequality for the polynomials having no zeros in |z| < 1, except s-fold zeros at the origin. Our result generalize certain well-known polynomial inequalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Concerning the inequalities for |D α P (z)| in terms of |P (z)| an interested reader may go through [9,11], [14]- [17]. Now, the following result is regarding the growth of polar derivative of a polynomial.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the inequalities for |D α P (z)| in terms of |P (z)| an interested reader may go through [9,11], [14]- [17]. Now, the following result is regarding the growth of polar derivative of a polynomial.…”
Section: Resultsmentioning
confidence: 99%
“…There exist number of results in the literature as refinements and generalizations of inequalities of (1.6) and (1.7) in various ways for references see [9,11,17,18]. Aziz and Rather [3] considered a more general case for investigating the dependence of P (Rz) − βP (rz) q on P q for every β ∈ C with |β| ≤ 1, R > r ≥ 1, q > 0 and extended inequality (1.8) for 0 < q < 1 as following.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these generalizations involve the comparison of polar derivative D β P (z) with various choices of P (z), β and other parameters. The latest research and development on this topic can be found in the papers ( [5,8,10,11,[13][14][15][16]20]).…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, we see that inequalities have been extended from ordinary derivative to polar derivative of polynomials, and for some of the recent research and developments in this direction, one can consult the papers ( [6], [11]- [16], [19], [20]). As a polar derivative generalization of (3), Aziz and Rather [1] proved that if P (z) is a polynomial of degree n having all its zeros in |z| ≤ k, k ≤ 1, then for every complex number α with |α| ≥ k,…”
Section: Introductionmentioning
confidence: 99%